PENERAPAN MODEL PEMBELAJARAN GENERATIF TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK SMP - Dinny Mardiana; Enung Elda Martina (Universitas Islam Nusantara, 2017)
Generatif learning model was expected to be an alternative to increase student’s mathematical communication ability. The purpose of the research to determine the improvement of student’s mathematical communication ability after using Generatif learning model, the influence of generative learning models on improving mathematical communication skills, and the response to student’s the generative learning model. This research method used quasi-experiment with non equivalent pretest-posttest control group design. The research’s subject was VIII-C as experimental class and VIII-G as a control class which chosen as purposive sampling. The research instruments were tests, observation sheets and questionnaires. The research conclude that student’s mathematical communication abiliy class research have increased significantly compared to the control class. It finds based on the average score N-gain on every mathematical communication indicators. The influence of Generative learning model toward the increasing students’ mathematical communication ability at experimental class is high interpretation. It indicates that Generative learning model has positive influence to student’s mathematical communication ability. In addition, students’ responnse to Generative learning model are positive.